Pengaruh Strategi Keterikatan terhadap Kinerja Karyawan melalui Keterikatan Karyawan dan Perilaku Kewargaan Organisasi pada Karyawan Milenial - Machdania Zulkarnain; Tjahjani Prawitowati; Nurcholis Setiawan (MAMEN: Jurnal Manajemen, 2024)
It is important for companies to manage employee performance well by understanding the antecedent variables that can build and improve employee performance. This research aims to examine the role of employee engagement strategies, employee engagement, and organizational citizenship behavior in building millennial employee performance. The population in this research is millennial employees in Surabaya. Sampling was carried out purposively with the criteria being that the employee's work period was at least one year. From data collection through questionnaires, one hundred and twenty-five respondent data was obtained which could be processed. Data analysis uses Structural Equation Model-Partial Least Square (SEM-PLS). The results of this research show that employee engagement strategies have a significant effect on employee performance, employee engagement has a significant effect on organizational citizenship behavior, organizational citizenship behavior has a significant effect on employee performance. The results of this research also show the influence of engagement strategies on employee performance which is mediated by employee engagement and organizational citizenship behavior. Employee engagement and organizational citizenship behavior partially mediate the influence of employee engagement strategies on performance. As a practical implication of the results of this research, companies can develop employee performance by implementing engagement strategies with consistency, commitment and sustainability by preparing and implementing employee engagement and organizational citizenship behavior development programs.